Teaching Replication to Graduate Students. (October 2019) - Stojmenovska, Dragana; Bol, Thijs; Leopold, Thomas
Replicating published studies promotes active learning of quantitative research skills. Drawing on experiences from a replication course, we provide practical tips and reflections for teachers who consider incorporating replication in their courses. We discuss teaching practices and challenges we encountered at three stages of a replication course: student recruitment, course structure and proceedings, and learning outcomes. We highlight that by engaging in replication, students learn from established scholarly work in a collaborative and reflective manner. Students not only improve their quantitative literacy but also learn more generally about the scientific method and the production of research.